MAQÂSHID AL-SYARÎ’AH AL-SYÂTHÎBÎ (Sebuah Upaya untuk Menyingkap Tujuan Asasi Formulasi Hukum Islam) - Abdul Jalil Abdul Jalil (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2011)
Abstract: The al-Qur’ân is the only source of law by muslims believed to contain the rules guidelines and guidence to live in the word and the hereafter. Understand it (al-Qur’ân) requires a skill as well expertise, especially in the filed of linguistics  (rule lughâwiyyah) so as to understand the meaning of the word of god as defailed in the al-qur’ân. But god’s law is written in mushhaf sheets are also has the meaning that can be understood from what is implied  behind the text, a fundamental goal (maqâshid al-syarî’ah) of legal provisions in nashshîyyah. In the article the author wants to give an alternative understanding of the idea of a reformer of islamic legal thought that al-Syâthîbî in maqâshid al-syarî’ah outlines in his monumental work. Entitled al-muwâfaqât fî usûl al-syarî’ah . Whit this idea, the observer of islamic law is expected in understanding the law of god is not mely because there is an assessment tekts, but also expected more attention to and consider the fundamental purpose of the establishment of law of god. Key Words: al-Qur’ân, maqâshid al-syarî’ah, al-Syâthîbi, dan mashlahah